STRATEGI KREATIF CONTENT CREATOR DALAM MENINGKATKAN ENGAGEMENT RATE MELALUI KONTEN DIGITAL MEDIA SOSIAL INSTAGRAM @FATIHKOSOFFICIAL - Aulia Nur Alzena, Azzahra; Santoso, Hudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of social media has encouraged companies to create content strategies that build audience interaction. PT Fatih Amanah Sejahtera uses Instagram @fatihkosofficial as its main platform to market products and reach students. This study aims to analyze the creative strategies of content creators in increasing engagement rates. The research used a qualitative descriptive method through observation, active participation, interviews, documentation, and Instagram insight analysis during the internship period from January to May 2026. The results show that content management was carried out through planning, production, distribution, and evaluation stages. The strategies were analyzed using the Dimensions of Consumer Engagement theory by Brodie et al. (2013) The findings indicate that these creative strategies increased content relevance, expanded audience reach, and encouraged organic interaction.